Apocalypse-cinema : 2012 and other ends of the world - Szendy, Peter (Fordham University Press, 2015)
Apocalypse-cinema is not only the end of time that has so often been staged as spectacle in films like '2012', 'The Day After Tomorrow', and 'Terminator'. By looking at blockbusters that play with general annihilation while also paying close attention to films like 'Melancholia', 'Cloverfield', 'Blade Runner', and 'Twelve Monkeys', this book suggests that in the apocalyptic genre, film gnaws at its own limit.